A TOOLKIT TO EVALUATE THE IMPACT OF AN EDUCATIONAL ACTION TO SENIORS’ QUALITY OF LIFE - Esteller-Curto, Roger; Escuder-Mollon, Pilar; Ochoa, Luis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
When an institution needs to evaluate the teaching-learning process then it can be done evaluating the knowledge and skills acquired by the learners or by the self-evaluating the trainers from the students perspective. The qualifications in this context is the main measure to get the metric for evaluation. On the other hand, when there is not a need to acquire a specific knowledge or expertise but when the learners wants to continue learning because he/she enjoys it, wants to keep learning and being active or any other personal motivation, then evaluation becomes a big challenge. This is the case of seniors’ education (citizens over 65 or retired). Which metrics should be used when evaluating institution? how we can know if those institutions are doing the work correctly ? how can the institution increase the quality and effectiveness ? From this need the project QEduSen (supported by the Lifelong Learning Programme of the European Commission) produced an evaluation toolkit.